Efficacy and safety of Tuina (Chinese Therapeutic Massage) for knee osteoarthritis: A randomized, controlled, and crossover design clinical trial - Liu, Kaoqiang; Zhan, Yunfan; Zhang, Yujie; Zhao, Ye; Chai, Yongli; Lv, Hua; Yuan, Weian (Frontiers in Medicine, 2023)
Background Knee osteoarthritis (KOA) is a highly prevalent joint disease among the middle-aged and elderly population that can lead to pain, functional impairment, decreased quality of life, and a large number of medical expenses. Physical therapy is one of the main treatment methods for KOA. In China, Tuina has been widely used in the treatment of KOA, but up to now, there is no high-quality medical evidence to support its effectiveness and safety. The purpose of this study was to objectively evaluate the efficacy and safety of Tuina in the treatment of KOA. Methods A crossover design clinical trial was performed on 96 patients. The test group and the control group in the trial were allocated randomly in a ratio of 1:1. The test group received Tuina treatment for 4 weeks first and then received health education intervention for another 4 weeks. The control group received health education intervention for 4 weeks first and then received Tuina treatment for another 4 weeks. The Western Ontario and McMaster Universities Arthritis Index (WOMAC) total score was chosen as the primary outcome. The WOMAC pain score, WOMAC stiffness, WOMAC daily activity score, and visual analog scale (VAS) score were the secondary outcomes. Adverse events during the intervention were collected in both groups. Results Compared with the baseline, the WOMAC total score, WOMAC pain score, WOMAC stiffness, WOMAC daily activity, and VAS score of patients in both groups were improved significantly at weeks 4 and 8 (p < 0.001). All patients who received Tuina treatment were significantly superior to those who received health education intervention in the WOMAC total score (194.96, 95% CI = 164.94–224.97, P < 0.001), WOMAC pain score (45.96, 95% CI = 35.82–56.09, P < 0.001), WOMAC stiffness (31.42, 95% CI = 26.37–36.46, P < 0.001), WOMAC daily activity (117.58, 95% CI = 97.56–137.61, P < 0.001), and VAS score (1.07, 95% CI = 0.83–1.32, P < 0.001). Both groups had no serious adverse events during the treatment. Conclusion This trial demonstrated that Tuina can reduce joint pain in patients with KOA and improve the physical functions of the knee joint effectively and safely. Clinical trial registration This trial was registered in the Chinese Clinical Trial Registry (No. ChiCTR-TTRCC-13003157). http://www.chictr.org.cn/showproj.aspx?proj=6402.